Pd-Catalyzed Regioselective Tandem C–S/C–N Bond Formation for Modular Synthesis of Pyrimidine-Fused Benzothiazoles from o-Dihaloarenes and 3,4-Dihydropyrimidin-2-thiones - Hu, Xuying; Liu, Ruiqi; Fu, Shiwen; Shi, Lianxu; Chen, Chunxia; Peng, Jinsong (Synthesis, 2024)
A Pd-catalyzed annulation reaction for the synthesis of 4H-pyrimido[2,1-b]benzothiazole derivatives via regioselective tandem C–S/C–N bond formation was developed. With PdCl2(PPh3)2 as the precatalyst, Davephos as the ligand, and K2CO3 as the base, the reactions of various 3,4-dihydropyrimidin-2-thiones with o-dihaloarenes proceeded smoothly, and the desired products were obtained in moderate to good yields.
Keywords: palladium catalysis; annulation; C–S bond formation; C–N bond formation; o-dihaloarenes; pyrimidobenzothiazoles